Tinjauan Literatur Terkini Tentang Wakaf - Fauzi, Muhammad; Efendi, Faisal; Bundo, Mayang; Eriawati, Yossi; Rahmat, Fawza (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to review the latest literature on waqf and highlight directions for future research. This research is qualitative research, with the data search method used is literature review. The data source for this research is literature about waqf, which was collected through search in the Emerald data base for the last 20 months (January 2022 – August 2023), by entering the keyword title in the search column